Characterisation of Allicin Activity in Candida Albicans - Khodavandi, Alireza (2011)
Candidiasis is a term describing infections by yeasts from the genus Candida, and the type of infection encompassed by candidiasis ranges from superficial to systemic.Treatment of such infections often requires antifungals such as the azoles, but increased use of these drugs has led to selection of yeasts with increased resistance to these drugs. Essential oils such as allicin are an example of natural compounds which when used in synergy with antimicrobial agents may increase the efficacies of these therapeutic agents. In the present study, it is hypothesized that allicin has antifungal effect against different genera and species of fungi including Candida spp. and allicin acts via suppressing some of the virulence attributes of Candida. For determination of minimal inhibitory concentration (MIC) of allicin against Candida spp., a standard broth dilution method (NCCLS-M27 A2) was used. The determination of fractional inhibitory concentration (FIC) for combination of allicin with fluconazole and ketoconazole was performed. The results showed a significant synergistic effect between allicin combined with azoles in some of the Candida spp. This demonstrates that allicin decreased the growth of C. albicans almost as efficiently as fluconazole (p < 0.05). For the murine model of candidiasis, female BALB/c mice, 4-6 weeks old, were inoculated intravenously via the lateral tail vein with C. albicans. Infection was followed up for 4 weeks and evaluated in terms of mortality, the latter being assessed by determination of fungal colonization of viscera. Fluconazole was also tested as a comparative standard antifungal drug. It has been shown that the allicin treated group (5mg/kg/day) was compatible to fluconazole treated group in terms of the fungal load reduction in kidney and spleen (p < 0.001) as well as improvement in the survival time (50% reduction in mortality) during 28 days period. For quantification of biofilm of Candida (treated and untreated), Crystal Violet and XTT assays have been performed. Results showed a significant reduction of biofilm in C. albicans treated with allicin. On the other hand, the morphological changes of biofilms treated with allicin at different concentrations have been observed with scanning electron microscopy (SEM) and compared to normal biofilms. The presence of pits on the cell surface and cellular collapse with high concentrations of allicin indicates that the cell membrane could be one of the targets of allicin in Candida. In order to observe the effect of allicin on hyphae production and biofilm formation, measurement of expression of SAP1-4, SIR2 (hyphae) and HWP1, INT1 (biofilm) genes after treatment with allicin has been conducted through semi quantitative RT-PCR and then relative real time RT-PCR. RNA was extracted and converted to cDNA, which was used as a template in RT-PCR.These significant results have demonstrated the strong down-regulated expression of SIR2 and HWP1 genes at 5.54 and 138.889 fold changes respectively (p < 0.0001), after treatment with allicin along with observation of suppression of hyphae and biofilm via SEM. For evaluation of ERG3, ERG 11 (Ergosterol) and CDR1 (ABC Transporter) expression after treatment by allicin, semi quantitative RT-PCR was used for investigating the effect of allicin on expression of membrane-related genes. These results were significant for fluconazole (down-regulated expression) but allicin-treated samples did not show any significant change in gene expression for ERG3, ERG 11 and CDR1. Taken together, it can be concluded from the results in this study that allicin displays significant efficacy when applied in synergy with fluconazole and ketoconazole. Results from the in vivo mouse model of systemic candidiasis also indicated that allicin is able to reduce fungal load and prolong the survival time. In conclusion, HWP1 and SIR2 genes are suggested as the targets of allicin in Candida cells.